2010
DOI: 10.1111/j.1523-5378.2010.00803.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Statin Therapy Affects the Severity of Chronic Gastritis

Abstract: Long-standing statin therapy may reduce the severity of chronic gastritis. Mild increased CRP levels in absence of obvious source can predict the severity of chronic gastritis. Further researches are needed to assess the effect of statin in chronic gastritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…Although the therapeutically beneficial effects of statins in these diseases are generally attributed to their cholesterol-lowering action, the results from an increasing number of in vitro and in vivo studies indicate that statins also have anti-inflammatory effects that are independent of their hypocholesterolemic activity [2,3]. Statins have also been reported to have immunomodulatory, antioxidative, and antithrombotic actions [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Although the therapeutically beneficial effects of statins in these diseases are generally attributed to their cholesterol-lowering action, the results from an increasing number of in vitro and in vivo studies indicate that statins also have anti-inflammatory effects that are independent of their hypocholesterolemic activity [2,3]. Statins have also been reported to have immunomodulatory, antioxidative, and antithrombotic actions [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Depletion of cellular cholesterol not only attenuates H. pylori -induced pathogenesis (Hutton et al, 2010; Lai et al, 2011) but also promotes autophagy (Cheng et al, 2006), which has been shown to contribute to immune defense against invading pathogens (Levine et al, 2011; Deretic et al, 2013; Lai et al, 2015). Statins, inhibitors of HMG-CoA reductase that are widely prescribed for lowering serum cholesterol, have also been employed to reduce the risk of certain bacterial infections (Chow et al, 2010; Nseir et al, 2010; Boyd et al, 2012; Motzkus-Feagans et al, 2012). The in vitro and ex vivo approaches utilized in this study provided evidence that statin treatment results in reduced bacterial burden in macrophages, and consequently attenuation of H. pylori pathogenesis, via activation of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that statins are used to reduce the risk of some bacterial infections, including Chlamydia pneumonia [51], Clostridium difficile [52], H. pylori [53], Streptococcus pneumonia [54] and Staphylococcus aureus [55]. These findings shed light on the novel approach that inhibition of cellular cholesterol may be useful to inhibit bacteria-induced pathogenesis.…”
Section: Future Perspectivementioning
confidence: 90%